Luteolin attenuates LPS-induced damage in IPEC-J2 cells by enhancing mitophagy via AMPK signaling pathway activation - Yuan, Jianyun; Zhang, Ke; Yang, Lingling; Cheng, Xinyi; Chen, Jinyan; Guo, Xiaoquan; Cao, Huabin; Zhang, Caiying; Xing, Chenghong; Hu, Guoliang; Zhuang, Yu (Frontiers in Nutrition, 2025)
BackgroundLuteolin (LUT), a flavonoid compound widely present in natural plants, has been extensively studied for its diverse biological properties, involving anti-inflammatory,antioxidant, anti-apoptosis and other properties.MethodsThe aim of this study was to investigate the effect of LUT on lipopolysaccharide (LPS)-induced Intestinal Porcine Epithelial Cell line–J2 (IPEC-J2 cells) damage and its underlying mechanism.ResultsThe experiment showed that LPS treatment induced injury in IPEC-J2 cells, leading to tight junction disruption, ROS accumulation, and cell apoptosis. Remarkably, LUT attenuated LPS-induced IPEC-J2 cells damage by the up-regulation of Zonula Occludens–1(ZO-1), Occludin, and Claudin protein 1 (Claudin-1) protein expression levels.Besides, LUT increased the activities of CAT, and SOD and prevented LPS-induced MDA and ROS production. LUT suppressed Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation in LPS-induced IPEC-J2 cells, reducing (Interleukin-1beta) IL-1β and Interleukin–6 (IL-6) expression. Moreover, LUT attenuated LPS-induced apoptosis in IPEC-J2 cells by up-regulating expression of B-cell lymphoma 2 (Bcl-2) and down-regulating expression of Cysteine-aspartic acid protease 3 (Caspase-3), Cysteine - aspartic acid protease 9 (Caspase-9) and Bcl-2-associated X protein (Bax). Furthermore, LUT upregulated the AMP–activated protein kinase (AMPK)/Unc–51 like autophagy activating kinase (ULK) signaling pathway and Parkin–RBR E3 ubiquitin protein ligase (Parkin)/PTEN induced putative kinase 1 (PINK1)–mediated mitophagy in a dose–dependent manner. When AMPK was knocked down by short–hairpin RNA (shRNA), the protective effects of LUT against LPS–induced IPEC–J2 cell damage were weakened, as evidenced by the accumulation of excessive ROS and impaired mitophagy.ConclusionIn summary, LUT exhibits the ability to protect against LPS-induced damage to intestinal tight junctions by enhancing mitophagy through AMPK activation.